(RETRACTION) Arah Baru Pendidikan Islam: Membangun Epistemologi Pendidikan Islam Monokhotomik - Zamrony Zamrony (Hikmah: Journal of Islamic Studies, 2017)
RETRACTION TO: Zamroni (2017). Arah Baru Pendidikan Islam: Membangun Epistemologi Pendidikan Islam Monokhotomik. Hikmah: Journal of Islamic Studies, 13(2), 1-34. This article has been retracted by Publisher based on the following reason: The Editor of HIKMAH Journal found the double publication in the article publishing due to article's content similarity published in DINAMIKA ILMU Vol 10, No. 2 (2010) URL: https://journal.iain-samarinda.ac.id/index.php/dinamika_ilmu/article/view/45. Titled” Arah Baru Pendidikan Islam: Membangun Epistemologi Pendidikan Islam Monokhotomik” with the same author who is Zamrony. Based on clarification, Author of the article have admitted that she has published the same article published in DINAMIKA ILMU Vol 10, No. 2 (2010). One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.